2020
DOI: 10.1123/jsep.2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

Role Commitment and Acceptance in a Sport Context

Abstract: The objectives of this study were to (a) develop a conceptualization of role acceptance, later situated within the broader concept of role commitment, pertinent to the sport environment; (b) develop a measure integrating direct perceptions of role commitment and the bases of this variable; and (c) determine if role commitment could predict athletes’ intentions to return. To accomplish these objectives, multiple methods were used across 4 projects that leveraged the extant literature on acceptance and commitmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…Another notable limitation was that cohesion was only examined as an antecedent of role commitment despite suggestions that the relationship may be reciprocal in nature (Bray et al, 2002; Carron & Eys, 2012; Eys et al, 2020). In particular, two qualitative studies exploring role perceptions in the team sport environment suggested that cohesion and commitment to role responsibilities may be have a reciprocal relationship (Benson et al, 2013; Holt & Sparks, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another notable limitation was that cohesion was only examined as an antecedent of role commitment despite suggestions that the relationship may be reciprocal in nature (Bray et al, 2002; Carron & Eys, 2012; Eys et al, 2020). In particular, two qualitative studies exploring role perceptions in the team sport environment suggested that cohesion and commitment to role responsibilities may be have a reciprocal relationship (Benson et al, 2013; Holt & Sparks, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In Study 1, we sought to determine if cohesion perceptions could predict the bases of role commitment and, in turn, if the bases were related to direct perceptions of role commitment over two time points in a Canadian youth sport sample. Study 2 examined the same theoretical path as Study 1 over two time points (cohesion predicting the bases of role commitment and, subsequently, the bases relating to direct perceptions of role commitment) with the addition of examining whether direct perceptions of role commitment were further associated with intentions to return to sport (Eys et al, 2020) ). The competition level of the teams ranged from the first tier division to the third tier division of regional-level competition.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations